The role of developmental assets in childhood career development. Issue 2 (9th March 2022) - Kim, Hyunhee; Carney, JoLynn V.; Guo, Xiuyan; Prescod, Diandra J.
Abstract: This study examined hope as a mediator between school connectedness and childhood career development. Participants included 456 elementary school students in Grades 4 through 6. The results of structural equation modeling supported the hypothesized mediation model, indicating that school connectedness leads to childhood career development both directly and indirectly via hope. The findings suggest that when children feel connected to school, they are likely to demonstrate a greater level of hope, which in turn leads to enhanced career development. The results of this study highlight the importance of developmental assets in promoting childhood career development and has important implications for counseling practice in school settings.